2019
DOI: 10.1108/sr-02-2019-0051
|View full text |Cite
|
Sign up to set email alerts
|

Modeling for prediction of surface roughness in milling medium density fiberboard with a parallel robot

Abstract: Purpose This paper aims to discuss the utilization of artificial neural networks (ANNs) and multiple regression method for estimating surface roughness in milling medium density fiberboard (MDF) material with a parallel robot. Design/methodology/approach In ANN modeling, performance parameters such as root mean square error, mean error percentage, mean square error and correlation coefficients (R2) for the experimental data were determined based on conjugate gradient back propagation, Levenberg–Marquardt (LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…For this purpose, a confirmation experiment by using the Taguchi optimization technique was performed. Equation (6) was used in order to find the optimum surface roughness [30]: (6) where (A 1 , B 3 , and C 1 ) show the optimal-level mean values of surface roughness (Ra opt ) in Table 2 and T Ra declares the 7. According to these equations, the minimum surface roughness can be found as 2.022 μm.…”
Section: Optimization Of Surface Roughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, a confirmation experiment by using the Taguchi optimization technique was performed. Equation (6) was used in order to find the optimum surface roughness [30]: (6) where (A 1 , B 3 , and C 1 ) show the optimal-level mean values of surface roughness (Ra opt ) in Table 2 and T Ra declares the 7. According to these equations, the minimum surface roughness can be found as 2.022 μm.…”
Section: Optimization Of Surface Roughnessmentioning
confidence: 99%
“…Diverse machining processes such as drilling, milling, and turning are applied to obtain the required size and form of the MDF [1][2][3][4]. e most common technique for examining machining efficiency is based on the surface finishing and covers visual evaluation of surface quality measurement [5,6]. Nowadays, especially, algorithms based on experimental design are used to optimize various engineering problems [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the surface roughness can be optimized with a higher cutting speed and lower feed rate values. Based on the analysis of variance, Ayyildiz [12] found the most effective parameter affecting the surface roughness is the depth of cut while the factor ranked second is cutting the speed. Li et al [13] investigated the effects of input parameters on specific cutting energy during the MDF helical up-milling process.…”
Section: Introductionmentioning
confidence: 99%
“…In the milling process, the surface roughness is one of the important properties indicating workpiece quality. Models used in the prediction of surface roughness include the multiple regression technique, fuzzy set-based technique, and artificial neural networks (ANNs) [3][4][5][6][7]. e prediction of surface roughness (Ra) values in Al alloy 7075-T7351 in the face milling machining process for different ANNs was developed by Munoz-Escalona and Maropoulo [8].…”
Section: Introductionmentioning
confidence: 99%